Kutiyattam Sanskrit theater of India - Richmond, Farley P., 1938- (University of Michigan Press, 2002)
Multimedia presentation on Kutiyattam, a genre of theater dating back to the tenth century C.E. which is associated with Hindu temple life and religious ritual. Includes text, images, video, and audio related to various dimensions of Kutiyattam performances.